2011
DOI: 10.1007/s12020-011-9444-7
|View full text |Cite
|
Sign up to set email alerts
|

An association of interleukin-10 gene polymorphisms with Graves’ disease in two Chinese populations

Abstract: Graves' disease (GD) is a common autoimmune disorder with a genetic predisposition. The cytokine interleukin-10 (IL-10) has a central role in mediating inflammation, which may affect the outcome of the patients with GD. To elucidate the impact of IL-10 gene polymorphisms, we performed a two-stage case-control association study of five single-nucleotide polymorphisms (SNPs) within the IL-10 gene as well as a meta-analysis of two SNP's rs1800896 and rs1800872 covering three previous studies from Iran, Taiwan, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…This may be further evidence towards an association of the locus with the disease. Physiologically, our finding is in accordance with results published elsewhere which attribute the status of ‘high-producer' of circulating IL10 to the -1082A allele [41,42], contributing to the rationale that suppression or attenuation of neuroinflammation in susceptible subjects may protect against the onset of AD. The -1082 SNP is in complete linkage disequilibrium, with variances at other positions also allegedly functional as the -819 T/C (rs1800871) and the -592 C/A (rs1800872) SNPs, yielding promoter haplotypes already implicated in the risk for AD [43,44] and others that deserve proper investigation by subsequent genomic approaches.…”
Section: Discussionsupporting
confidence: 92%
“…This may be further evidence towards an association of the locus with the disease. Physiologically, our finding is in accordance with results published elsewhere which attribute the status of ‘high-producer' of circulating IL10 to the -1082A allele [41,42], contributing to the rationale that suppression or attenuation of neuroinflammation in susceptible subjects may protect against the onset of AD. The -1082 SNP is in complete linkage disequilibrium, with variances at other positions also allegedly functional as the -819 T/C (rs1800871) and the -592 C/A (rs1800872) SNPs, yielding promoter haplotypes already implicated in the risk for AD [43,44] and others that deserve proper investigation by subsequent genomic approaches.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, Chu reported that a non-synonymous single-nucleotide polymorphism rs40401 (P27S) of the interleukin 3 ( IL3 ) gene was associated with increased risk of GD [36]; Guo found the rs568408 polymorphism in the interleukin-12 ( IL-12 ) gene was also associated with increased risk of GD [37]. In addition, polymorphisms in the ADRB2 gene [3], interleukin-10 ( IL-10 ) gene [38], TNF-α gene [39] were also found to be associated with GD in Chinese population. These genes were all suggested as the candidate genes for GD in Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the IL-10 can alter the structure and quantity of this gene, and consequently influencing the expression and function of the product. Previous studies have demonstrated that IL-10 genetic polymorphisms could affect the risk of many autoimmune diseases, such as rheumatoid arthritis, systemic lupus erythematosus, Graves' disease and peptic ulcer (Sugimoto et al, 2007;Liu et al, 2011;da Silva et al, 2004;Lagha et al, 2015). Sugimoto et al (2007) carried out a study in a Japanese population, and reported that IL-10 -1082/-819/-592 haplotypes were correlated with an elevated risk for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Sugimoto et al (2007) carried out a study in a Japanese population, and reported that IL-10 -1082/-819/-592 haplotypes were correlated with an elevated risk for gastric cancer. Liu et al (2011) investigate the role of the IL-10 genotype polymorphism in susceptibility to Graves' disease, and demonstrated that IL-10 -1082 genetic polymorphism was significantly correlated with Graves' disease susceptibility in the Chinese population. da Silva et al (2014) carried out a study in a Brazilian population, and reported that the IL-10 -1082 genetic polymorphism may influence the systemic lupus erythematosus susceptibility.…”
Section: Discussionmentioning
confidence: 99%